Pomacentrus aurifrons, a new species of damselfish (Pomacentridae) from Melanesia - Allen, Gerald R. (Zootaxa, 2004)
A new species of pomacentrid fish is described from coral reefs of Papua New Guinea. Specimens were collected by the author between 1982 and 2000. Pomacentrus aurifrons is described from 12 specimens, 22.4 61.5 mm SL, collected at depths between 7 12 m. It closely resembles P. smithi Fowler and Bean from Indonesia and the Philippines. These species have similar morphology but are easily distinguished by the taller dorsal fin of P. aurifrons (tallest dorsal ray averaging 1.37 in HL versus 1.65 in HL for P. smithi) and colour pattern differences, particularly the broad zone of yellow encompassing the snout, forehead, and base of the anterior dorsal spines.